Closure of the patent foramen ovale in patients with embolic stroke of undetermined source: A clinical expert opinion and consensus statement for the Asian-Pacific region. Issue 9 (December 2020) - Diener, Hans-Christoph; Akagi, Teiji; Durongpisitkul, Kritvikrom; Thomson, Viji Samuel; Prabhakar, AT; Sharpe, Ross; Albers, Bert; Lewalter, Thorsten; Oki, Koichi; Sharma, Vijay K
Recently published long-term data from randomized controlled trials have provided evidence for the prevention of recurrent embolic stroke of undetermined source by percutaneous closure of the patent foramen ovale. However, most data were obtained from Caucasian populations and evidence on patent foramen ovale closure in Asian-Pacific patients is limited. The relative paucity in clinical data from this population, as well as the fact that Asian-Pacific patients may have higher bleeding risks than Caucasians, complicates clinical decision-making. This document, resulting from a consensus meeting of Asian-Pacific clinical experts, states the consensus among these experts about how to treat Asian-Pacific patients who had an embolic stroke of undetermined source and have a patent foramen ovale, based on currently available evidence and expert opinions. In addition, uncertainties and the need for clinical data regarding patent foramen ovale closure for prevention of recurrent embolic stroke of undetermined source in general, and specifically for Asian-Pacific patients, are identified.